Customer Satisfaction Mediates Repurchase Intention in Cloud Kitchens: Kepuasan Pelanggan Berperan sebagai Mediator dalam Niat Membeli Kembali di Dapur Awan - Maida, Salsabilla; Safirin , Mochamad Tutuk (Academia Open, 2026)
General Background: Indonesia’s food and beverage industry is expanding rapidly, particularly with the rise of cloud kitchen concepts such as Hangry. Specific Background: Nevertheless, this growth is accompanied by a decline in sales and the emergence of negative customer feedback, which suggests potential weaknesses in product quality, service delivery, brand image, and promotional efforts. Knowledge Gap: Existing research on repurchase intention shows inconsistent results and rarely investigates these variables simultaneously within the cloud kitchen environment. Aims: Therefore, this study aims to examine the impact of product, service quality, brand image, and promotion on repurchase intention, with customer satisfaction acting as a mediating variable. Novelty: This study offers a new perspective by combining the cloud kitchen context with the use of Generalized Structured Component Analysis (GSCA) to analyze complex interrelationships among variables. Results: Based on GSCA-SEM analysis involving 100 respondents, the results indicate that not all variables directly influence repurchase intention, while customer satisfaction plays a significant mediating role. Implications: These findings underline the importance of enhancing product consistency, improving service quality, strengthening brand image, and optimizing promotional strategies to increase customer satisfaction and encourage repeat purchases.. Highlights: • Customer satisfaction functions as a crucial mediator in repurchase intention. • Not all independent variables directly impact repurchase intention. •The cloud kitchen setting provides deeper insights into consumer behavior. • GSCA is suitable for examining complex models with relatively small sample sizes. Keywords: Repurchase Intention, Customer Satisfaction, Brand Image, Cloud Kitchen, GSCA SEM